(untitled) - Iddittie, Junesay (Tokyo, 1955)
The immediate post-war years in Japan are frequently referred to as the yakeato jidai or 'burned-out ruins period.' Photographs from this time show a panorama of skeletal buildings amidst piles of rubble. Ragamuffin children, many of them orphans, play barefoot while adults scavenge among the ruins for anything that might be bartered or put to use: tools, clothing, pots, and most importantly, food. An enormous number of city dwellers had lost everything in the war. Indeed, as historian Igarashi Yoshikuni points out, for many survivors, their bodies were the only things that they had managed to preserve from the air raids.[1] With the collapse of the militarist regime there was a widespread rejection of the 'spiritual' wartime ideology that had been used to justify privation and self sacrifice. Instead, the needs of the body or the 'flesh' (nikutai) played much on people's minds, giving rise to a popular literary genre, 'literature of the flesh' (nikutai bungaku), that graphically depicted the physical needs of embodied existence.
Keywords: Nhật Bản,Japan; Nền văn minh,Ảnh hưởng của Mỹ,Civilization,American influences